Overcoming the incumbency and barriers to sustainable cooling - Lizana, J; Miranda, ND; Gross, L; Mazzone, A; Cohen, F; Palafox-Alcantar, G; Fahr, P; Jani, A; Renaldi, R; McCulloch, M; Khosla, R (Ubiquity Press, 2022)
This article examines cooling in the built environment, an area of rapidly rising energy demand and greenhouse gas emissions. Specifically, the status quo of cooling is assessed and proposals are made for how to advance towards sustainable cooling through five levers of change: social interactions, technology innovations, business models, governance and infrastructure design. Achieving sustainable cooling requires navigating the opportunities and barriers presented by the incumbent technology that currently dominates the way in which cooling is provided—the vapour-compression refrigerant technology (or air-conditioners). Air-conditioners remain the go-to solution for growing cooling demand, with other alternatives often overlooked. This incumbent technology has contributed to five barriers hindering the transition to sustainable cooling: (1) building policies based exclusively on energy efficiency; (2) a focus on temperature rather than other thermal comfort variables; (3) building-centric design of cooling systems instead of occupant-centric design; (4) businesses guided by product-only sales; and (5) lack of innovation beyond the standard operational phase of the incumbent technology. Opportunities and priority actions are identified for policymakers, cooling professionals, technicians and citizens to promote a transition towards sustainable cooling.